Fiber isolated from discarded fruits and vegetables reduces valproic acid-induced hepatotoxicity in rats - Maria Rosana Ramirez; Debora Manuale; Juan Carlos Yori (Brazilian Journal of Pharmaceutical Sciences)
Abstract In this work, a methodology was developed to obtain dietary fiber from agro-industrial fruit and vegetable waste. The resulting raw material was named DF. The physicochemical analysis revealed a high total dietary fiber content, along with an appropriate soluble to insoluble fiber ratio and excellent water and fat retention capacity. Subsequently, its potential protective effect against hepatotoxicity induced by valproic acid (VPA) was investigated in Wistar rats, both as preventive and curative treatments. For this purpose, two different trials were conducted. In the preventive trial, VPA (250 mg/kg/day; oral) was administered concomitantly with DF (0.3 and 0.15 mg/kg/day) for 14 days. In the curative trial, VPA was administered for 14 days, followed by DF for an additional 14 days. The results demonstrated that DF supplementation normalized body weight, liver biomarkers and attenuated VPA-induced tissue damage, while normal liver architecture was preserved. These findings suggest that DF obtained from agro-industrial fruit and vegetable waste materials may serve as a functional feedstock to counteract the harmful effects associated with prolonged VPA treatment.